LCD versus CRT Monitors for Digital Mammography: A Comparison of Observer Performance for the Detection of Clustered Microcalcifications and Masses. - Joo Hee Cha; Woo Kyung Moon; Nariya Cho; Eun Hye Lee; Jeong Seon Park; Mi Jung Jang (Acta Radiologica, 2009)
Background: There are two types of soft-copy display of digital mammograms, cathode-ray tube (CRT) and liquid-crystal display (LCD) monitors, and these present different resolutions and noise characteristics. Purpose: To compare observer performances for the detection of clustered microcalcifications and masses in digital mammograms, using LCD and CRT monitors. Material and Methods: Four radiologists evaluated 100 digital mammograms. Of these, 28 mammograms depicted clustered microcalcifications (12 benign, 16 malignant), 18 depicted masses (10 benign, eight malignant), and 54 depicted no apparent abnormality. The images were stored uncompressed as Digital Imaging and Communications in Medicine (DICOM) files and randomized for two sessions of soft-copy reading. The readers independently read all cases displayed on two 5-megapixel LCD and two CRT monitors with an interval of 3 months. Observers were asked to rate using a five-point scale the likelihoods of microcalcifications and masses independently. Receiver operating characteristic analysis was used to analyze results. Results: For the LCD and CRT monitors, average area-under-the-curve (Az) values for microcalcification detection were 0.977 (0.976, 0.970, 0.980, and 0.983 for the four readers) and 0.958 (0.910, 0.990, 0.976, 0.956), respectively. Corresponding Az values for masses were 0.971 (0.955, 0.990, 0.949, 0.989) and 0.944 (0.928, 0.966, 0.955, 0.925). No statistically significant difference was detected between the two monitor types (P>0.05). Conclusion: The LCD and CRT monitors are comparable in terms of detecting clustered microcalcifications and masses in digital mammograms.